Factors predicting the probability of estrus and pregnancy - T. Goehring; L. Corah; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1987)
A statistical analysis was used to determine which live animal traits are useful in predicting reproductive performance in first-calf heifers. Heifer condition score at calving and change in condition score postcalving, calving difficulty score, and milk production were related to the probability of estrus and pregnancy. Condition score at calving had the greatest impact and, to a great extent, moderates the influence of the other traits.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Estrus; Pregnancy; Performance